Use of gen-probe probe competition assay as a supplement to probes for direct detection of Chlamydia trachomatis and Neisseria gonorrhoeae in urogenital specimens. - Woods, G L (1996)
The potential for development of a cost-effective protocol for selective use of the Gen-Probe probe competition assay (PCA) in conjunction with PACE 2 for direct detection of Chlamydia trachomatis and Neisseria gonorrhoeae in urogenital specimens that would not compromise patient care was investigated. To accomplish this, PCA data from testing performed over 12 months were retrospectively reviewed. Of 237 samples that were presumptively positive for C. trachomatis by initial probe assay and could be tested by PCA, positive PCA results were obtained for 100, 79, and 59%, respectively, of specimens that gave a signal of more than 1,500, 1,000 to 1,500, and less than 1,000 relative light units (RLU). For the 141 specimens that were presumptively positive for N. gonorrhoeae and could be tested by PCA, positive PCA results were obtained for 99, 80, and 42%, respectively, of samples with a signal of more than 1,500, 1,000 to 1,500, and less than 1,000 RLU. These data indicate that PCA should be a routine supplement to Gen-Probe PACE 2 for specimens with an initial signal by probe assay of less than 1,500 RLU and may not be necessary for samples yielding a signal of more than 1,500 RLU.